Low-cost post-treatments improve the efficacy of hydrochar as peat replacement in growing media. Issue 5 (October 2018) - Dalias, Panagiotis; Prasad, Munoo; Mumme, Jan; Kern, Jürgen; Stylianou, Marinos; Christou, Anastasis
Abstract: Peatlands represent a valuable global carbon store and are critical for preserving biodiversity. In order to reduce peat mining a significant effort is made to search for substitutes of peat in its different uses. Organic products obtained by hydrothermal carbonization processes could fully or partially replace peat in growing media if they possess some suitable properties. The study focused on the properties of a hydrochar produced from wheat (HTC) and included its chemical characterization and stability estimates using microbial respiration and nitrogen mineralization essays. As inhibition to seed germination could significantly restrict the eventual use of HTC in growing media, a number of seed germination trials were carried out to reveal the magnitude of phytotoxicity in relation to sphagnum peat and biochar and the effect that some simple and low-cost pre-conditioning treatments have on the rate of germination. This rate was greatly increased by simply wetting the material a few days prior to use or by mixing it with compost. It was shown that the positive effect on seedling emergence should be attributed, at least partly, to the degradation by microorganisms of toxic substances presumably produced during carbonization.